The era of comfort, a threat to sufficiency? - Stefano Boni (Field Actions Science Reports)
Comfort is an essential part of contemporary life. Born in the 19th century, comfort is now omnipresent in every sphere of our existence, and tends to drastically diminish our sensory experience. This reduction in our sensory experience has numerous consequences for our individual lives, our health, our relationship with nature and the environment, according to the author, – insofar as it stems from an industrial model with harmful consequences (pollution, global warming...). Re-evaluating our relationship with technology and comfort in the light of our real needs, on a community scale, and reinvesting in artisanal techniques, can be levers of emancipation according to the author.